Organic fertilization of Christmas tree (Abies balsamea (L.) Mill.) plantations with poultry manure in northwestern New Brunswick, Canada - Manuel Lamontagne; Hector Guy Adégbidi; Abbé Jonas Assamoi (The Forestry Chronicle, 2019)
At the instigation of local growers, an experiment was conducted on balsam fir (Abies balsamea (L.) Mill.) Christmas tree plantations in northwestern New Brunswick, Canada. The objective was to compare poultry manure as an organic fertilizer to the commonly used commercial mineral fertilizer, and establish the rate and frequency of manure application. Six fertilization treatments were applied in a randomized block design monitored during five years: one control (0 g N), one mineral fertilizer treatment (20 g N tree-1 year-1 as 20-10-10 (NPK)) and four poultry manure applications ((4-1-2 NPK) 20 g N tree-1 year-1, 40 g N tree-1 year-1, 40 g N tree-1 every two years and 80 g N tree-1/2 yrs). Photosynthesis, soil respiration and specific leaf area were slightly increased by the manure treatments. Height and diameter relative growth rates were similar among fertilization treatments. Manure treated trees had nutritional status similar or better than mineral fertilizer treated trees. Manure treatments had the highest percentages of dark green foliage trees appreciated by buyers. Poultry manure was as efficient as the mineral fertilizer. Considering fertilizers and operations costs, the application of poultry manure at the rate of 40 g N tree-1 /2 yrs seemed the one to be recommended to growers.